2015
DOI: 10.1186/s40064-015-1426-4
|View full text |Cite
|
Sign up to set email alerts
|

A study of heat and mass transfer in a fractional MHD flow over an infinite oscillating plate

Abstract: Exact expressions of velocity, temperature and mass concentration have been calculated for free convective flow of fractional MHD viscous fluid over an oscillating plate. Expressions of velocity have been obtained both for sine and cosine oscillations of plate. Corresponding fractional differential equations have been solved by using Laplace transform and inverse Laplace transform. The expression of temperature and mass concentration have been presented in the form of Fox-H function and in the form of general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…How altering degree of radiation and temperature provision impacted flow dynamics along with properties of flow in porous medium were discussed by [33,34]. More recently, flow speed enhancing factors like induced shear on channel boundary was discussed in [35,36], through calculation of closed form solutions using fractional derivatives. Keeping the nature of polymeric fluids with memory effects in mind, the investigation of related fluid dynamics using slip boundary condition is considered to be imperative and has been discussed in our present article.…”
Section: Introductionmentioning
confidence: 99%
“…How altering degree of radiation and temperature provision impacted flow dynamics along with properties of flow in porous medium were discussed by [33,34]. More recently, flow speed enhancing factors like induced shear on channel boundary was discussed in [35,36], through calculation of closed form solutions using fractional derivatives. Keeping the nature of polymeric fluids with memory effects in mind, the investigation of related fluid dynamics using slip boundary condition is considered to be imperative and has been discussed in our present article.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the effects of high temperature insulation and heat radiation in MHD nanofluids in porous medium were determined in [26,27]. Some interesting results were also added to the literature regarding studying the dynamics of fluids with varying viscosity through fractional derivative approach [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al [14] reported the conjugate effect of heat and mass transfer on time fraction convective flow of Brinkman type fluid using the Caputo approach. Shahid et al [15] investigated the approach of Caputo fractional derivatives to study the magnetohyrodynamic (MHD) flow past over an oscillating vertical plate along with heat and mass transfer. Recently, Caputo and Fabrizio (CF) have initiated a fractional derivative with no singular kernel [16].…”
Section: Introductionmentioning
confidence: 99%